PRINCIPLES OF WATER INFRASTRUCTURE MANAGEMENT IN ENSURING SUSTAINABLE WATER USE IN UKRAINE - Nataliia Mahats (Agora International Journal of Economical Sciences (AIJES), 2023)
The military actions in Ukraine significantly aggravate the problems of sustainable water resources management. Even in the pre-war period, the main funds of the drinking water supply and sanitation systems were characterized by an unsatisfactory technical condition, an extremely high percentage of wear and tear and required large capital investments. During the wartime, the water management infrastructure of Ukraine became the object of massive attacks by the Russian Federation, which led to catastrophic consequences, such as the destruction of critical infrastructure facilities, lack of population access to drinking water supply, contamination of drinking water sources, complications of the sanitary and epidemiological situation, which poses a significant threat to the health of the nation.The purpose of the article is to determine the current state, trends in the restoration and development of the water management infrastructure in Ukraine and the formation of the basic principles of its management to ensure sustainable water use in Ukraine. The methodological tools of the study were such approaches and methods as a systematic approach, methods of system-structural analysis and synthesis, comparison and generalization, economic and statistical methods.
Keywords: 330